(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Issues of reliability, strength, durability and resource are the most important in modern technology. Due to ever-increasing demands to speed, efficiency, reliability and to reduce the weight of machines strength are becoming more and more complex. They must take into account various operating modes, real properties of materials, loading conditions, technological, operational and other factors.